Anaesthetic records. Issue 2 (February 2023) - Clark, Callum; Dickerson, Jonathan E.
Abstract: Record-keeping during the perioperative period by anaesthetists is a fundamental part of modern anaesthetic practice. This article explores the numerous functions of the anaesthetic record, and highlights the practice guidelines governing their suggested content. The advantages and disadvantages of an electronic record keeping system are also explored.